Pemanfaatan bahan baku lokal dalam pengembangan wisata Pulau Cinta di Desa Teluk Kenidai Kecamatan Tambang Kabupaten Kampar Provinsi Riau - Trisla Warningsih; Kusai Kusai; Lamun Bathara; Andarini Diharmi; Deviasari Deviasari (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2020)
Teluk Kenidai Village is located in Tambang District, Kampar Regency, Riau Province. Teluk Kenidai Village has the potential for natural tourism in the form of beaches, which are one of the alternative tourist destinations for the community. The activities carried out are playing various kinds of rides and swimming on the banks of the Kampar River. The visitors to the island of love in Kenidai Bay are the largest visitors of all tourist objects in Kampar Regency. The existence of the island of love tourism can develop the community's economy by providing special foods as souvenirs and drinks for tourist visitors. Alternative foods that can be done are processed crispy monitor fish and lime syrup drinks because these two things have very high potential in Kampar Regency, and can provide added value to people's lives. The purpose of the activity is to empower the people of Teluk Kenidai Village, to process various crispy monitoring fish and to increase the attractiveness of the island of love for visiting tourists. The benefits of the activity are opening up people's insights in increasing the potential of natural resources, gaining skills and abilities in making crispy monitor fish and lime syrup to improve the economy. The method is carried out by demonstration and hands-on practice in the manufacture of crispy monitoring fish and lime syrup. The target communities are the people living in Teluk Kenidai Village and village customary leaders and the Tourism Awareness Group (Pokdarwis) totaling 15 people. Evaluation is carried out by giving questionnaires to all participats before and after the delivery of counseling materials and practices. The results of the evaluation of the community service activities that have been carried out show that the increasing desire of the community in practicing extension activities to earn additional income by opening this bussines, especially in the tourist area of Pulau Cinta in Teluk Kenidai Village.